Implementasi Metode Visual-Auditory-Kinestetik dalam Tari Sigeh Penguten sebagai Tarian Tradisi Lampung - Apriyani Apriyani (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The purpose of learning the Sigeh Pengunten Dance with the VAK (Visual) learning method is to determine how students can demonstrate the Sigeh Penguten Dance according to what the teacher teaches. The research method used is descriptive qualitative with a population of UPTD SMPN 3 Metro students and a sample size of 5 students. The results of this study are that the learning process using the visual method, auditory kinesthetic in practice has increased from the first meeting to the eighth meeting. This research can be seen from 3 aspects of VAK, namely visual and auditory in the form of students listening to teacher instructions and paying attention and seeing the teacher demonstrating the Sigeh penguten dance, namely the Lapah tebeng movement, Seluang going home, jong simpuh, sitting down, jong silo Ratu and Sembah, flashback, biting. , samber floated. Guuh Gakhang, Ngiyau Bias, Makuraccang, Kenui floating and tipping at high levels, Sabung Hovering, reject slashing and splitting hui, able to bias, end to a moderate level and end to a low level, Lipetto and Jong Simpuh Sembah. Regarding the kinesthetic aspect of students dancing, the Sigeh Penguten dance With the various movements mentioned above, starting from the first meeting to the seventh meeting, the eight students took practical tests to take scores and evaluations. The value obtained from the practical test carried out increased understanding, which could be seen in the increase in the value obtained, although it decreased slightly at the third meeting. The results of the VAk learning test (Visual, auditory., Kinesthetic) as a whole show the data that students have been able to demonstrate the Sigeh Penguten dance with an average score of Good.